A review of software product line adoption - A. Jabar, Marzanah; Mohammadzadeh, Bahareh Zarei; Sidi, Fatimah; Mohd. Sani, Nor Fazlida (Asian Research Publishing Network, 2013)
Software Product Line was proposed in 2000 as a systematic approach toward reuse. Although benefits of this strategy is totally well known but there are still uncertainties between organizations about how they can apply SPL to their software product. This review tries to study articles in which adoption models and their properties were discussed in order to get a clear perspective about SPLs implementations and adoption strategy. This study is conducted as a Systematic Literature Review which was used to identify important characteristic which should be considered for product line adoption. 22 primary studies from different sources were evaluated to answer 2 research questions. The research identified more than 30 paper on this study but only 21 of them was precisely relevant in the field of SPL adoption. This research provides a general guideline for organization which wants to use SPL in their company. Our preliminary study conclude that in order to choose an appropriate adoption model organizations should identify their needs and choose best way according to that.